MANIFESTATION SPECIFICS OF RELIGIOUS IDENTITY OF DAGESTAN PEOPLES - Sahbanova, M M; Nurilova, A Z (History, Archeology and Ethnography of the Caucasus, 2015)
The article covers the place of religious identity of Dagestan people in the structure of social identity. The authors have ascertained the correlation of the types of social identity and indices of reproduction of religious identity.
Keywords: Dagestan faithful; Dagestan people; Islam; religious identity; religious orientation; Orthodoxy.